Power And Choice : An Introduction to Political Science - SHIVELY, W. Phillips (McGraw - Hill Book Company, 2003)
A general, comparative introduction to the major concepts and themes of political science. The basics are made affordable to students through concise presentation - offering a comparative approach to the subject, highlighted through case studies that offer real-world examples of political behaviour. This new edition includes a new chapter on democracy and the process of democratization (chapter 7), a new chapter on comparative legal systems (chapter 15), a thoroughly revised chapter on international relations (chapter 17), which discusses current theoretic concerns; and new materials on "The Pleasures of Politics" (chapter 1).